Effect of low temperature and room temperature on the depth of cure of bulk-fill composite resins (Bioscience Journal, 2023)
The study analyzed the influence of temperature on the depth of cure of bulk-fill composite resins. Three discs (ISO 4049/2000) from each group were made, and four restorative materials were investigated: Opus Bulk-Fill Flow, Opus Bulk-Fill APS, Filtek™ One Bulk-Fill, and Filtek™ Bulk-Fill Flow. They were light-cured (Gnatus ± 1,200 mW/cm2) for 20 seconds, varying the temperature (23°C and 5°C) and simulating the use of the product both at room temperature and under refrigeration. The materials were inserted in aluminum matrices with 10 mm in depth and 4 mm in diameter. A clear film strip and a glass microscope slide were positioned at the top and bottom surfaces. The material was condensed and light-cured with the tip of the light source in close contact, for 20 seconds on the top surface. Immediately after irradiation, the samples were removed from the mold, and the uncured part was removed with a plastic spatula. The measurement was performed with a micrometer ± 0.1 mm, and the value was divided by 2. The data were analyzed with two-way ANOVA at a significance of 0.05. There was a statistical difference in the temperature between the results obtained in Opus Bulk-Fill APS (p